In situ synthesis of polyynes in a polymer matrix via pulsed laser ablation in a liquid. Issue 8 (8th September 2020) - Peggiani, Sonia; Facibeni, Anna; Milani, Alberto; Castiglioni, Chiara; Russo, Valeria; Li Bassi, Andrea; Casari, Carlo S.
Abstract : Nanocomposites are based on polyynes synthesized by laser ablation of graphite directly in a solution of PVA. Abstract : Polyynes are finite chains formed by sp-hybridized carbon atoms with alternating single and triple bonds and display intriguing electronic and optical properties. Pulsed laser ablation in liquid (PLAL) is a well assessed technique for the physical synthesis of hydrogen-capped polyynes in solution; however, their limited stability prevents further exploitation in materials for different applications. In this work, polyynes in poly(vinyl alcohol) (PVA) were produced in a single-step PLAL process by ablating graphite directly in an aqueous solution of PVA which, as a participating medium for PLAL, is shown to favour the formation of polyynes. The addition of Ag colloids to the aqueous PVA/polyynes solution allowed surface-enhanced Raman spectroscopy (SERS) measurements, carried out both on liquid samples and on free-standing nanocomposites, obtained after solvent evaporation. A non-trivial behaviour of the polymer matrix structure as a function of the PVA concentration is revealed showing that an intimate blend of polyynes and Ag nanoparticles with the polymer can be achieved. We demonstrate that polyynes in the nanocomposite remain stable for at least 11 months, whereas the corresponding Ag/PVA/polyynes solution displayed a strong polyyne decomposition already after 3 weeks. These results pave the way to further characterization of the properties of polyyne-based films and materials.